WILLINGNESS TO PAY ON VISIT TO MUSEUM: A CONCEPT PAPER OF CHOICE MODELLING APPLICATION FOR NATIONAL MUSEUM OF MALAYSIA - Sarah Fahani Mohd Fadhil; Alias Radam; Mohd Rusli Ya’cob; Zaiton Samdin (Journal of Islamic, Social, Economics and Development, 2017)
museum is one of the cultural institutions which has profound economic impact in the sense that it serves as a way to fuel the creative energy that has become such an integral part of modern lives and can provide a boost to regional tourism. There are almost 100 public museums in Malaysia, and one of its most famous museums is Muzium Negara. In the early years, Muzium Negara is capable of attracting more than one million visitors to the museum annually. However the total number of visitors drops to 60 percent since the 1990s. While the current research acknowledges the demand of visiting museum as cultural destination, the majority of studies focus less on the investigation of visitor value on the museum. Clearly, there is a need to explore whether there are pertinent economic values towards Muzium Negara. Thus, choice experiment approach will be used as it offers a practical way of understanding visitor preferences to cultural attractions and then helps to develop strategies that would transform traditional visitors to be more frequent consumers. Four attributes in the categories facilities and service (Exhibition Setting Change, Multimedia Audio-Visual Interactive Service, Sign Interactive and web access about collection); and Management (Museum Information Package, Visitors’ Guide, Visitor Participation, and Customer Feedback System) will focus as visitor preferences whether there are willing to trade their preference with some entrée fee.